2018
DOI: 10.3892/mmr.2018.9590
|View full text |Cite
|
Sign up to set email alerts
|

Selenocysteine mimics the effect of dietary restriction on lifespan via SKN‑1 and retards age‑associated pathophysiological changes in Caenorhabditis�elegans

Abstract: Selenocysteine, a sulfur-containing amino acid, can modulate cellular oxidative stress defense systems by incorporating into anti-oxidant enzymes such as glutathione peroxidase and thioredoxin reductase. Selenocysteine can also prevent cancer, neurodegenerative diseases and cardiovascular diseases. A recent study revealed that dietary supplementation with selenocysteine can increase the resistance of Caenorhabditis elegans to environmental stressors and its lifespan. The objective of the present study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Resveratrol, a polyphenol compound rich in red wine, has been shown to have strong antioxidant and lifespan-extending effects on various model organisms [35]. Recent studies reported that amino acid derivatives, including N-acetyl-L-cysteine, S-allylcysteine, and selenocysteine, increase resistance to oxidative stress and extend lifespan in C. elegans [15, 16, 36]. In the present study, we showed that phosphatidylcholine, a phospholipid composing cellular membrane, had an antioxidant activity in vivo and conferred the longevity phenotype in C. elegans for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol, a polyphenol compound rich in red wine, has been shown to have strong antioxidant and lifespan-extending effects on various model organisms [35]. Recent studies reported that amino acid derivatives, including N-acetyl-L-cysteine, S-allylcysteine, and selenocysteine, increase resistance to oxidative stress and extend lifespan in C. elegans [15, 16, 36]. In the present study, we showed that phosphatidylcholine, a phospholipid composing cellular membrane, had an antioxidant activity in vivo and conferred the longevity phenotype in C. elegans for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…N-Acetyl-L-cysteine increased the resistance to environmental stresses and lifespan, mimicking dietary restriction [15]. Supplementation with selenocysteine conferred longevity phenotype and ameliorated age-related pathophysiological changes [16]. Extracts from Acanthopanax sessiliflorus , a plant used as a traditional treatment for many diseases, or Tenebrio molitor , an insect whose extracts have antibacterial, antifungal, and anticancer activities, also showed antioxidant and antiaging effect in C. elegans [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the latter, it was recently reported that in Caenorhabditis elegans , the Sec mimics the effects of caloric restriction, which has shown benefits in lifespan and in age-related diseases. In this study, Sec was shown to mimic the effects of calorie restriction through SKN-1, the ortholog of nuclear factor erythroid 2-related factor 2 (NRF2) in mammalians, which regulates the expression of antioxidant proteins [ 150 ]. Although some of the aforementioned therapies, such as the Mediterranean diet and fasting, have shown favorable effects on some parameters of RA, more robust clinical trials are needed to generalize their recommendation; however, they are still promising proposals for accompanying drug therapy in RA patients.…”
Section: Selenium Intake Recommendation and Its Rich Sourcesmentioning
confidence: 99%
“…Selenocysteine plays an important role in cellular oxidative stress defense systems and preventing neurovegetative diseases. Selenocysteine has recently been shown to mimic the effects of DR on lifespan and age‐related pathophysiological changes by SKN‐1 but is not dependent on DAF‐16 (Kim, Kim, & Park, 2018). Sesamin is derived from sesame seeds and exerts antiaging effects (Yaguchi et al., 2014).…”
Section: Caenorhabditis Elegans As a Powerful Model For Antiaging Evamentioning
confidence: 99%
“…d ‐allulose, an isomer of d ‐fructose, also increased the lifespan of nematodes and mimic DR response in the organism (Kim, Kim, & Park, 2018a). A study found that Ayurvedic polyherbal extract (PHE) at a low dose of 0.01 µg/mL increased the mean lifespan of C. elegans by 16.09% (Rathor, Pant, Awasthi, Mani, & Pandey, 2017).…”
Section: Caenorhabditis Elegans As a Powerful Model For Antiaging Evamentioning
confidence: 99%